Sounds of the other side: a look at the John Cage's silent music from Acoustic Ecology, hybridization and musicking - Leal, Sergio [UNESP] (Univ Federal Goias, 2020)
From the reflections on Cage's 4'33, we discuss the implications of the use of silence in music, its reverberations regarding to traditional concept of work, of Western classical music, and its potential to coping with the problem of excessive noise in contemporary life. The discussion is based on Cage's ideas, the concept of hybridization, by Canclini, on Schafer's Acoustic Ecology, and Small's concept of musicking. It is verified that excessive noise in current life is closely related to prevailing economic interests and has as one of its causes the survival of myth of progress and its materialization in the fetish of technology, neophilia and the use of sound as symbolic violence. We conclude that approach of silence from Cage, Schafer and Small offers a broad perspective to listening education through the adoption of an understanding of sound as an emancipated phenomenon, integrated into the context of life as a whole.
Keywords: Music; Silence; Acoustic Ecology; Hybridization; Musicking; Listening education